Stress, Coping Strategies and Social Support as Predictors of Mental Health of Police Personnel of North India - Singh, Shweta; Gupta, Bandna; Mishra, Premchandra (Indian Journal of Community Health, 2022)
Introduction: The profession of a police personnel is extremely stressful. Coping strategies and social support are known to be robust buffers of stress Objective: To study Stress, Coping Strategies and Social Support as Predictors of Mental Health of Police Personnel of Uttar Pradesh, North India. Method: This was a cross-sectional study comprising of 300 male police personnel. Assessment was done using Occupational Stress Questionnaire, Brief COPE Scale and Mental Health Inventory. Multiple Regression Analysis was used to analyze the data. Results: Ambiguity stress, the belonging and appraisal support are found to be the strongest predictor of mental health of constables. Stress in the area of organizational structure, the appraisal support and maladaptive coping strategies are essential predictors of mental health of inspectors. Beside this, social support, belonging support, appraisal support and active coping are significant predictor of mental health of Officers.